Short-term value growth of the acquirer in strategic M&A: Evidence from NASDAQ Helsinki - Salmela, Konsta (My University, 2024)
Mergers and acquisitions (M&A) are important and common strategies used by companies to e.g. enhance market power, expand product offerings and achieve operational efficiencies. They are crucial mechanisms for corporate growth and strategic realignment. This thesis studies the short-term impact of strategic acquisitions on shareholder value among Finnish companies listed on NASDAQ Helsinki, focusing on transactions valued at over $200 million from 2014 to 2023. The study encompasses a sample of 45 acquisitions. This research employs an event study methodology to examine stock price reactions to M&A announcements. The methodology is partly based on the Efficient market hypothesis (EMH), which posits that new information is rapidly reflected in stock prices. The analysis covers multiple event windows, from 10 days before to 10 days after the announcement, aiming to capture the immediate market response to these M&A events. The results of this study reveal a significant positive market reaction to large acquisition announcements. Specifically, the cumulative average abnormal return (CAAR) was 4.4% over a five-day period following the announcement. This reflects a strong initial investor response, with daily average abnormal returns (AAR) reaching approximately 2.5% on the announcement day. It is noteworthy that a 2.5% daily return can be considered exceptional for the entire sample, highlighting the notable investor enthusiasm and optimism regarding the anticipated benefits of these transactions. Additionally, positive abnormal returns continued into the following two days, demonstrating sustained investor enthusiasm and optimism about the expected benefits of the acquisitions. The study also found no statistically significant abnormal returns prior to the announcements, supporting the EMH and suggesting that investors did not have access to material non-public information. This indicates that the Finnish stock market accurately reflects publicly available information, reducing concerns about insider trading or information asymmetry affecting stock prices before the announcements. While the short-term results are promising, it is important to consider the sustainability of these value gains. Historical evidence indicates that many acquisitions fail to deliver the anticipated long-term benefits, often due to challenges such as integration issues, market changes, and shifts in competitive dynamics. Therefore, while the initial positive reaction is encouraging, a thorough evaluation of the long-term impacts on the acquiring company’s value is crucial for understanding the true success of the acquisition. To conclude, this thesis highlights the immediate positive effect of significant M&A announcements on shareholder value in Finland, emphasizing the role of strategic acquisitions in enhancing market perception and investor confidence. However, it also stresses the need for caution regarding the long-term outcomes of such transactions.

Yritysostot ja fuusiot (M&A) ovat tärkeitä ja yleisiä strategioita, joita yritykset käyttävät muun muassa markkinavoiman lisäämiseen, tuotevalikoiman laajentamiseen ja operatiivisten tehokkuuksien saavuttamiseen. Ne ovat tärkeitä tapoja mahdollistaa yritysten kasvu ja strategiset uudelleenjärjestämiset. Tässä tutkimuksessa tutkitaan strategisten yritysostojen lyhyen aikavälin vaikutuksia osakkeenomistajien arvoon suomalaisilla NASDAQ Helsingissä listatuilla yrityksillä, keskittyen yli 200 miljoonan dollarin arvoisiin tapahtumiin vuosina 2014–2023. Tutkimus kattaa 45 yrityskauppaa. Tämä tutkimus toteutettiin käyttäen hyödyksi tapahtumatutkimusta, joka tutkii osakekurssien reaktioita yrityskauppojen ilmoitusten ympärillä. Metodologia perustuu osittain myös tehokkaiden markkinoiden hypoteesiin (EMH), joka väittää, että uusi tieto heijastuu nopeasti osakekursseihin. Analyysi kattaa useita tapahtumavälejä, 10 päivää ennen ja 10 päivää jälkeen ilmoituksen, minkä tavoitteena on tarkastella välitöntä markkinareaktiota näihin yritysostoihin. Tutkimuksen tulokset osoittavat verrattain merkittävän positiivisen markkinareaktion suuriin yrityskauppailmoituksiin. Erityisesti kumulatiivinen epänormaali tuotto (CAAR) oli 4,4 % viiden päivän aikana ilmoituksen jälkeen. Tämä tulos heijastaa voimakasta alkuperäistä sijoittajareaktiota, päivittäisten keskimääräisten epänormaalien tuottojen (AAR) saavuttaessa noin 2,5 % ilmoituspäivänä. Huomioitavaa on, että koko otoksen osalta 2,5 % päivätuotto on poikkeuksellinen, mikä korostaa sijoittajien suurta innostusta ja optimismia kauppojen odotettujen hyötyjen suhteen. Lisäksi on mainitsemisen arvoista, että positiiviset poikkeamat jatkuivat seuraavina päivinä, mikä osoittaa jatkuvaa sijoittajien innostusta ja optimismia näiden yritysostojen odotettujen hyötyjen suhteen. Tutkimuksessa ei havaittu tilastollisesti merkittäviä poikkeamia ennen ilmoituksia, mikä tukee EMH ja viittaa siihen, että sijoittajilla ei ollut pääsyä olennaiseen ei-julkiseen tietoon. Tämä viittaa siihen, että suomalainen osakemarkkina heijastaa tarkasti julkisesti saatavilla olevaa tietoa, vähentäen huolia sisäpiirikaupasta tai tiedon epäsymmetriasta osakekursseihin ennen ilmoituksia. Vaikka lyhyen aikavälin osalta tuotot ovat lupaavia, on tärkeää harkita toteutuneen arvonnousun kestävyyttä. Historialliset todisteet viittaavat siihen, että monet yritysostot eivät saavuta odotettuja pitkän aikavälin hyötyjä, usein johtuen esimerkiksi integraatiohaasteista, markkinamuutoksista ja kilpailudynamiikan muutoksista. Siksi, vaikka alun positiivinen reaktio on rohkaiseva, perusteellinen arviointi yrityskaupan pitkäaikaisista vaikutuksista ostavan yrityksen arvoon on tärkeää todellisen vaikutuksen ymmärtämiseksi. Yhteenvetona voidaan todeta, että suuret yritysostoilmoitukset ovat tuottaneet välitöntä positiivista vaikutusta osakkeenomistajien arvoon Suomessa, ja tämä korostaa yritysostojen merkitystä markkinanäkemyksen ja sijoittajaluottamuksen lisäämisessä. Siitä huolimatta pitkän aikavälin tulosten osalta on otettava huomioon myös muita tekijöitä ennen kuin voidaan todeta yritysoston todella onnistuneen.
Keywords: Mergers and acquisitions, Finnish M&A, event study, accounting and finance